2018
DOI: 10.22159/ijpps.2018v10i10.25124
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiplasmodial and Cytotoxic Activities of a Sungkai (Peronema Canescens) Leaf Extract

Abstract: Objective: The aim of this study was to assess the antiplasmodial and cytotoxic activities and to evaluate the selectivity indices of acetone, ethanol and aqueous extracts of Peronema canescens leaves. Methods:Antiplasmodial activity was measured in vitro against Plasmodium falciparum strains D10 and FCR3 by 72 h incubation at 37 °C in a candle jar. Parasitaemia was calculated by counting the parasite numbers in thin smears. In vitro cytotoxicity was assayed in Vero cells using 3-(4,5dimethylthiazol-2-yl)-2,5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…According to [36], their research proved that the administration of PC leaf extract up to 0.75 mg/kg BW to Mus musculus as an animal test on the parameter period of organogenesis resulted in no statistically significant effect on how the fetus of animal test grew or changed on the outside. This study found that PC leaves extract usage at a maximum dose of 0.75 mg/kg BW was safe.…”
Section: Teratogenicmentioning
confidence: 99%
“…According to [36], their research proved that the administration of PC leaf extract up to 0.75 mg/kg BW to Mus musculus as an animal test on the parameter period of organogenesis resulted in no statistically significant effect on how the fetus of animal test grew or changed on the outside. This study found that PC leaves extract usage at a maximum dose of 0.75 mg/kg BW was safe.…”
Section: Teratogenicmentioning
confidence: 99%
“…The other research on anti-malarial potential of sungkai plant was done by Swandiet al (2018) by giving leaves extract of the plants grown in South Sumatra to the two PlasmodiumfalciparumstrainsD10andFCR3wich were maintained in vitro in human eritrocytes cultures. After the parasite and extract were mixed an incubated for 72 h at 37 o C, apparently, both Plasmodium strains experienced significant growth inhibition.In this experiment, the researchers tested three kinds of extracts at once, namely: acetone, ethanol, and water extracts.Among the three types of extract they used, the water extract showed the best result [8].…”
Section: Antimalarialmentioning
confidence: 99%
“…In addition, flavonoid compounds and tannins, which belong to the group of phenolic compounds and generally have antioxidant activity, will have a mutually reinforcing effect 39&40 . In addition, P. canescens leaves were reported to have several pharmacological activities, including immunostimulant 41 , anti-inflammatory 42 antidiabetic 25 , antiplasmodial 43 , and antihyperuricemia 44 . However, further research is needed to prove these activities.…”
Section: Quantitative Antioxidant Activity Test Of P Canescens Leaves...mentioning
confidence: 99%